(3.1) … … …
![(\mathrm dy)/(\mathrm dx) = (2x-y)/(x-2y)](https://img.qammunity.org/2022/formulas/mathematics/college/7gvk9l489cewlnxfua5ovenzvxxbmtrgke.png)
Multiply the right side by x/x :
![(\mathrm dy)/(\mathrm dx) = \frac{2-\frac yx}{1-\frac{2y}x}](https://img.qammunity.org/2022/formulas/mathematics/college/pa7gb8e9rakdeb5onzala39rbct2o7itrh.png)
Substitute y(x) = x v(x), so that dy/dx = x dv/dx + v :
![x(\mathrm dv)/(\mathrm dx) + v = (2-v)/(1-2v)](https://img.qammunity.org/2022/formulas/mathematics/college/19f00il6cbb9inalosixndgccsxkguq5iz.png)
This DE is now separable. With some simplification, you get
![x(\mathrm dv)/(\mathrm dx) = (2-2v+2v^2)/(1-2v)](https://img.qammunity.org/2022/formulas/mathematics/college/cjbpoowtd2v20voj4wvqbptqseaksgpd05.png)
![(1-2v)/(2-2v+2v^2)\,\mathrm dv = \frac{\mathrm dx}x](https://img.qammunity.org/2022/formulas/mathematics/college/2uqw3fy1qm8fa53eo0viqpa1kwj1yoi640.png)
Now you're ready to integrate both sides (on the left, the denominator makes for a smooth substitution), which gives
![-\frac12\ln\left|2v^2-2v+2\right| = \ln|x| + C](https://img.qammunity.org/2022/formulas/mathematics/college/fjir714186remtzr1ogn49cq4hztnt3pe7.png)
Solve for v, then for y (or leave the solution in implicit form):
![\ln\left|2v^2-2v+2\right| = -2\ln|x| + C](https://img.qammunity.org/2022/formulas/mathematics/college/pmtdmru8ru7krgmu4nlhcszzudfasb92yw.png)
![\ln(2) + \ln\left|v^2-v+1\right| = \ln\left(\frac1{x^2}\right) + C](https://img.qammunity.org/2022/formulas/mathematics/college/dzja5z9mc31xggn1xkro7rwltq2ng7eo27.png)
![\ln\left|v^2-v+1\right| = \ln\left(\frac1{x^2}\right) + C](https://img.qammunity.org/2022/formulas/mathematics/college/lwi7gjxtv5bnw3uwgw5eub1eqljg18rx7u.png)
![v^2-v+1 = e^(\ln\left(1/x^2\right)+C)](https://img.qammunity.org/2022/formulas/mathematics/college/vq2zy8kfxfgdvftvopp2bhvhyfkr4l98nv.png)
![v^2-v+1 = \frac C{x^2}](https://img.qammunity.org/2022/formulas/mathematics/college/w2mscmxhtl0itv9tuxd8j24gpud50yl3dg.png)
![\boxed{\left(\frac yx\right)^2 - \frac yx+1 = \frac C{x^2}}](https://img.qammunity.org/2022/formulas/mathematics/college/e2ktxa0iv534l3wpxuubanv5myez22zivf.png)
(3.2) … … …
![y' + \frac yx = (y^(-3/4))/(x^4)](https://img.qammunity.org/2022/formulas/mathematics/college/okk5w5boony3yuyo2svwcbj2a2nuo0wj7t.png)
It may help to recognize this as a Bernoulli equation. Multiply both sides by
:
![y^(3/4)y' + \frac{y^(7/4)}x = \frac1{x^4}](https://img.qammunity.org/2022/formulas/mathematics/college/brs6ed29k2d1bd3vicsg1vp9oxx1sf1lig.png)
Substitute
, so that
. Then you get a linear equation in z, which I write here in standard form:
![\frac47 z' + \frac zx = \frac1{x^4} \implies z' + \frac7{4x}z=\frac7{4x^4}](https://img.qammunity.org/2022/formulas/mathematics/college/o8s0q2bzg858l0lfzvrjg1v02mgd5whmvv.png)
Multiply both sides by an integrating factor,
, which gives
![x^(7/4)z'+\frac74 x^(3/4)z = \frac74 x^(-9/4)](https://img.qammunity.org/2022/formulas/mathematics/college/efwdjmo8s7nmvmgzpaxefguvotzpir58v0.png)
and lets us condense the left side into the derivative of a product,
![\left(x^(7/4)z\right)' = \frac74 x^(-9/4)](https://img.qammunity.org/2022/formulas/mathematics/college/g19t2gbvjpn4gnctbxjv1aklha7qc3rfet.png)
Integrate both sides:
![x^(7/4)z=\frac74\left(-\frac45\right) x^(-5/4)+C](https://img.qammunity.org/2022/formulas/mathematics/college/wfhwlobtkflp6h9weu2l59kwadnq4bq8e1.png)
![z=-\frac75 x^(-3) + Cx^(-7/4)](https://img.qammunity.org/2022/formulas/mathematics/college/kqeqhov05lyzx64570pvpe47om3djwguo8.png)
Solve in terms of y :
![y^(4/7)=-\frac7{5x^3} + \frac C{x^(7/4)}](https://img.qammunity.org/2022/formulas/mathematics/college/7n2u0jkcv1swm4hyd5zla1dw53z6u12t4k.png)
![\boxed{y=\left(\frac C{x^(7/4)} - \frac7{5x^3}\right)^(7/4)}](https://img.qammunity.org/2022/formulas/mathematics/college/krxgql5aarxytfv725zxzauvbg0cp6z7cs.png)
(3.3) … … …
![(\cos(x) - 2xy)\,\mathrm dx + \left(e^y-x^2\right)\,\mathrm dy = 0](https://img.qammunity.org/2022/formulas/mathematics/college/givq8jwszpwloo5isa6640tsbgiyfn47zd.png)
This DE is exact, since
![(\partial(-2xy))/(\partial y) = -2x](https://img.qammunity.org/2022/formulas/mathematics/college/gnrhabm2aiyt28roskvrwinp84nn71y3cz.png)
![(\partial\left(e^y-x^2\right))/(\partial x) = -2x](https://img.qammunity.org/2022/formulas/mathematics/college/px47oiaeka7ie167fv2cr80lofjdeuqz5m.png)
are the same. Then the general solution is a function f(x, y) = C, such that
![(\partial f)/(\partial x)=\cos(x)-2xy](https://img.qammunity.org/2022/formulas/mathematics/college/4kwb7l3cioneua66rf8v4m5pn6p94i0d6z.png)
![(\partial f)/(\partial y) = e^y-x^2](https://img.qammunity.org/2022/formulas/mathematics/college/3iwkqokrxarwq4q0fdugepl5t1a4mz5hux.png)
Integrating both sides of the first equation with respect to x gives
![f(x,y) = \sin(x) - x^2y + g(y)](https://img.qammunity.org/2022/formulas/mathematics/college/cxjkit4a6jzcnqt4kkl84110fvx03cv37f.png)
Differentiating this result with respect to y then gives
![-x^2 + (\mathrm dg)/(\mathrm dy) = e^y - x^2](https://img.qammunity.org/2022/formulas/mathematics/college/6s1pfelgxfa7r03hfhcd4b2p131bpaw12k.png)
![\implies(\mathrm dg)/(\mathrm dy) = e^y \implies g(y) = e^y + C](https://img.qammunity.org/2022/formulas/mathematics/college/c8qszkuyiaku1zga6pbpxz106lyovo6rez.png)
Then the general solution is
![\sin(x) - x^2y + e^y = C](https://img.qammunity.org/2022/formulas/mathematics/college/7yjc6j95ijxwsyycdc8u8pnm248mdnlljl.png)
Given that y (1) = 4, we find
![C = \sin(1) - 4 + e^4](https://img.qammunity.org/2022/formulas/mathematics/college/tyiuj6sv40dbpkfbey50wdh6x753xiurq8.png)
so that the particular solution is
![\boxed{\sin(x) - x^2y + e^y = \sin(1) - 4 + e^4}](https://img.qammunity.org/2022/formulas/mathematics/college/sgg9m2q7soyj219pfv96m0vtod23pohi23.png)